Healthcare Management and Quality during the First COVID-19 Wave in a Sample of Spanish Healthcare Professionals - Patricia Torrent-Ramos; Víctor M. González-Chordá; Desirée Mena-Tudela; Laura Andreu Pejó; Celia Roig-Marti; María Jesús Valero-Chillerón; Águeda Cervera-Gasch (MDPI AG, 2021)
The aim of this study was to assess how the healthcare professionals in the Castellón Province (Spain) perceive healthcare quality and management during the first COVID-19 wave. A cross-sectional study was carried out. An online survey on healthcare quality and management during the first COVID-19 wave was sent to healthcare professionals. Almost half of the sample believed that healthcare quality worsened during the first COVID-19 wave (45.3%; n = 173). Heavier workload (m = 4.08 ± 1.011) and patients' complexity (m = 3.77 ± 1.086) were the factors that most negatively impacted healthcare quality. Health department 3, primary care center, and other doctors assessed human and material resources management as significantly worse (p < 0.05). Human and material resources management and the healthcare organization negatively affected healthcare quality during the first COVID-19 wave. Significant differences were observed according to departments, services, and professionals.